IMPLEMENTASI E-COMICS PORTABLE SEBAGAI INOVASI MEDIA PEMBELAJARAN BAHASA INDONESIA - Nurhayatin, Titin; Marlia, Marlia; Fauziyyah, Desti Fatin (JURNAL PESONA, 2018)
AbstractLearning media is important element in the learning. Teachers must be able to choose, prepare, use, and develop the learning media for the achievement of learning goals. This study examines the effectiveness of portable e-comics as an innovative alternative media in Indonesian Language learning in grade 7th. The research method Â is R & D (define, design, develop, and disseminate). The effectiveness of portable e-comics used validity tests: relevance, consistency, adequacy, and attractiveness. The results of statistical tests that show the average value of the increase from pretest to postest (N-Gain) is 0.8187. It is mean that the level of understanding of portable e-comics material has increased with high category. So, based on the results of this study, portable e-comics effectively used as an alternative media in Indonesian Language learning in grade 7th. Keywords: portable e-comics, media, innovation